An Approach for Plasma Cell Myeloma Diagnosis by Two-Color Flow Cytometry Based on Kappa/Lambda Ratios of CD38-Gated Plasma Cells. (April 2013) - Nakayama, S.; Yokote, T.; Hirata, Y.; Iwaki, K.; Akioka, T.; Miyoshi, T.; Takayama, A.; Nishiwaki, U.; Masuda, Y.; Ikemoto, T.; Tanaka, H.; Nishimura, Y.; et al.
Criteria from the World Health Organization (WHO) are commonly used to diagnose plasma cell myeloma (PCM), but they are complex and require several laboratory parameters. To differentiate reactive plasmacytosis from clonal plasma cell neoplasms, such as PCM, it is important to accurately determine the expression of the cytoplasmic immunoglobulin (cIg) light chain (LC). Through retrospective analyses, we selected the patients with PCM, and analyzed records of 52 PCM patients, who underwent bone biopsies, and final diagnosis of PCM was established according to WHO criteria, and 22 controls. In the present study, all samples were analyzed by flow cytometry (FC) in the side scatter vs CD38 histogram mode, and the CD38-gated plasma cell population was identified. The positive cell ratios of kappa and lambda to plasma cell populations were analyzed. PCM cells were distinguished from normal plasma cells by a cut-off level between 0.80 and 3.3, a sensitivity of 90.3%, and a specificity of 81.1%. Two-color FC analysis is simple to perform, inexpensive, and clinically relevant data are obtained soon after completion of the FC measurements. It could be one of the helpful tools in the diagnosis of PCM. The correct diagnosis of PCM can be achieved more simply, efficiently, and rapidly by combining this method.